Gestão de resíduos de construção civil : avaliação e propostas de metodologias de gestão - Campos, Priscilia Benites de (2012)
The generation of construction and demolition (C&D) waste has increased worldwide in recent years. Given this reality, many countries have implemented or adapted its environmental laws in order to improve their performance on this issue, and has been growing interest in academia for developing management alternatives that may assist municipalities in this task. In Brazil, the Conama Resolution 307/2002 and more recently the National Policy on Solid Waste establish guidelines for proper management of these wastes. However, until now, most municipalities is far short of the law requirements. One cause of this is the lack of information that support decision-making on the best alternatives for the management of C&D waste and the establishment of effective and objective actions in this task, which should be specific for each municipality as a result of the peculiarities that each presents. Therefore, it is essential to carry out a diagnosis of management of these wastes, which provides information on the characteristics of the municipality, on the C&D waste generated therein, about the actions of existing C&D waste management, as well as on the level of compliance with legislation C&D waste by the municipality. Thus, in view of this need, the present study aimed to develop a method for performing diagnostic management of C&D waste that enables the development of an Integrated Management Plan of C&D Waste objective and effective in meeting the legislation and a generic model for the development of this plan, allowing constant updating of diagnosis for improving the management of such waste. To develop the diagnostic method, tools were used as process mapping, Ishikawa Diagram and 5W1H, which allowed the identification of the requirements necessary to meet the legislation on C&D waste and the causes of management problems, and action planning needed to prepare the plan. And to develop the model of the Integrated Management Plan of C&D Waste, was used as the basis ISO 9001:2008, which allowed a process approach and thus establish more objective actions. Then, to validate the developed method, we conducted a case study in the municipality of Angra dos Reis, from which it was established that the method provides the information that was intended and, as expected, you can?t get a initial diagnosis of C&D waste management that allows the implementation of a fully Integrated Management Plan of C&D Waste that meets the laws. However, from the initial diagnosis, the plan must be implemented within existing possibilities and, thereafter, it will be possible to obtain more accurate information to enable their continuous improvement, until it reaches its fullness.